(untitled) (El Hilo de la Fabula, 2023)
This article presents some ideas on the issue of women and women writers in migration literature, especially the notion of "migrant women writers", some topics developed in migration narrative, the implications of the choice of a writing language, and the consideration of migration literature within comparative literature.